Modelling sustainability - Todorov, Vladislav; Marinova, Dora (Elsevier Science, 2010)
The article presents a general classification of the models being developed in the area of sustainability arguing that the existing models represent the historical conceptualisation of sustainability starting from environmental constraints and moving towards economic valuation and social behaviour and policies. Coupled with computer power, sophisticated models with a varying levels of complexity have also been developed (static/dynamic; local/global; specific/general). However as any model is a simplification of the complex reality, the main purpose of any sustainability modelling (and the newly emerging area of sustainometrics) should be to allow dynamic representation, including the co-evolution of the sustainability systems and the role of humans as sustainability guardians.